Menumbuhkan Minat Baca Dan Kreativitas Di SDN Program Literasi Yang Menghasilkan Generasi Pemimpin Masa Depan - Mutia Amanda; Vina Yunita; Violandari Violandari; Yulianti Yulianti; Febrina Dafit (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to analyse the implementation of literacy programs in three primary schools, namely SDN 8 Bandar Laksamana, SDN 14 Teluk Mesjid and SDN 92 Pekanbaru. The research method used was observation and document analysis of literacy activities conducted by these schools. The results show that the three schools have implemented various types of literacy, such as literacy in reading and writing, digital literacy, science literacy, financial literacy, numeracy literacy and cultural-civic literacy. Through habituation, development and learning, students are given the opportunity to develop literacy skills holistically. Keywords relevant to this study are literacy, literacy program, primary school, observation, document analysis. This study shows that the successful implementation of literacy programs is supported by the commitment and efforts of schools in providing varied literacy experiences and actively involving students. The literacy programs help students improve their skills in reading, writing, using digital technology, understanding science, managing finances, understanding mathematics, and appreciating culture and citizenship. The findings provide important insights for educators and policy makers in improving the quality of basic education and students' literacy development.